Asynchronous video messaging promotes family involvement and mitigates separation in neonatal care. Issue 2 (14th September 2020) - Kirolos, Sandy; Sutcliffe, Lynsey; Giatsi Clausen, Maria; Abernethy, Carolyn; Shanmugalingam, Shanthi; Bauwens, Nicole; Orme, Judith; Thomson, Kirsty; Grattan, Rosemary; Patel, Neil
Abstract : Objective: To evaluate the parent and staff experience of a secure video messaging service as a component of neonatal care. Design: Multicentre evaluation incorporating quantitative and qualitative items. Setting: Level II and level III UK neonatal units. Population: Families of neonatal inpatients and neonatal staff. Intervention: Use of a secure, cloud-based asynchronous video messaging service to send short messages from neonatal staff to families. Evaluation undertaken July–November 2019. Main outcome measures: Parental experience, including anxiety, involvement in care, relationships between parents and staff, and breastmilk expression. Results: In pre-implementation surveys (n=41), families reported high levels of stress and anxiety and were receptive to use of the service. In post-implementation surveys (n=42), 88% perceived a benefit of the service on their neonatal experience. Families rated a positive impact of the service on anxiety, sleep, family involvement and relationships with staff. Qualitative responses indicated enhanced emotional closeness, increased involvement in care and a positive effect on breastmilk expression. Seventy-seven post-implementation staff surveys were also collected. Staff rated the service as easy to use, with minimal impact on workload. Seventy-one percent (n=55) felt the service had a positive impact on relationships with families. Staff identified the need to manage parental expectations in relation to the number of videos that could be sent. Conclusions: Asynchronous video messaging improves parental experience, emotional closeness to their baby and builds supportive relationships between families and staff. Asynchronous video supports models of family integrated care and can mitigate family separation, which could be particularly relevant during the COVID-19 pandemic. Abstract : This multi-centre evaluation of asynchronous video messaging in UK neonatal units using quantitative and qualitative methods, suggests that it can improve parental experience, build supportive relationships between families and staff, and support models of family integrated care.